Is an association of acro-osteolysis, bone fragility, and enchondromatosis a newfound disease caused by an amplification of PTHLH? A case report - Stéphane Echaubard; Céline Pebrel-Richard; Aurélie Chausset; Jean-Louis Kemeny; Etienne Merlin; Fanny Laffargue (BMC, 2022)
Abstract Background Acro-osteolysis (AO) refers to resorption of the distal finger and toe phalanges. It displays two patterns: (i) diffuse AO and (ii) transverse or bandlike AO. AO can be a sign of local distress (e.g. of toxic origin), but is very often a sign of a constitutional or systemic acquired disorder. Case presentation A 15-year-old girl was referred to a paediatric rheumatologist for recurrent pain in her fingertips. She presented a particular cross-sectional AO associated with the presence of intraosseous cysts and bone fragility with atypical fractures. Initial laboratory tests and radiological examination did not allow an etiological diagnosis. Genetic studies revealed a 12p11.22-p11.23 microduplication of 900 kb including the PTHLH (parathyroid hormone-like hormone) gene, which encodes for a hormone involved in the regulation of endochondral ossification and differentiation of chondrocytes, via its PTHLH receptor. Conclusions To date, 12p11.22-p11.23 duplications have been reported in five families with skeletal abnormalities, and in particular AO and enchondromatosis associated with bone fragility. This new observation, added to the other reported cases, suggests a close relationship between the presence of this microduplication and the skeletal abnormalities found in the patient. We suggest the descriptive name ABES (acro-osteolysis, bone fragility and enchondromatosis syndrome) to designate this disorder.